Marine sentinels using eDNA to track Physalia sp. in the Gulf of Thailand - Thanaporn Suebsuya; Panagiotis Madesis; Chatmongkon Suwannapoom; Maslin Osathanunkul (PLoS ONE, 2025)
Physalia sp. is among the world’s most hazardous marine species, posing a significant threat to public safety and Thailand’s tourism sector. Traditional survey methods such as trawling and netting are time-consuming, potentially disruptive to marine ecosystems, and often lack the precision needed for effective monitoring. This study employed environmental DNA (eDNA) analysis to investigate the distribution of Physalia sp. across 45 sampling sites in eight provinces along the Gulf of Thailand. Using species-specific primers and probes targeting the COI region, we successfully detected Physalia sp. eDNA in four provinces: Chonburi, Rayong, Chumphon, and Songkhla. Notably, high eDNA concentrations were observed in Songkhla province, correlating with direct beach observations and public health warnings. The detection in Chumphon province represents a previously undocumented distribution area for this species in Thailand. Bayesian occupancy modeling revealed moderate true-positive detection rates for field samples (θ11 = 0.627) and high rates for qPCR replicates (p11 = 0.9), with notably low false-positive probabilities (θ10 = 0.008, p10 = 0.01), demonstrating the reliability of our eDNA-based approach. These findings demonstrate the utility of eDNA technology as a non-invasive, sensitive tool for monitoring hazardous marine species, with important implications for public safety and marine ecosystem management.